Transformasi Digital di Pedesaan: Evaluasi Implementasi Sistem Informasi Desa di Kabupaten Seram Bagian Barat - Hatala, Rifaldi; Latuconsina, Nurainy (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
Digital transformation in rural areas is a crucial part of efforts to improve transparent and accountable village governance. This study aims to evaluate the implementation of the Village Information System (SID) in West Seram Regency, particularly in villages within Kairatu District, with a focus on identifying challenges and formulating strategic recommendations. This research employs a qualitative method with a case study approach, involving in-depth interviews, participatory observations, and document analysis related to SID implementation. The findings reveal various challenges in SID implementation, including the lack of supportive local regulations, limited human resource capacity, inadequate information technology infrastructure, and suboptimal performance of pilot applications. These challenges significantly affect the effectiveness of SID implementation at the village level. As a recommendation, strategic steps are needed, such as the formulation of local regulations supporting digital transformation, increased investment in information technology infrastructure, and training and capacity development for human resources at the village level. This study contributes to the development of social sciences and humanities, particularly in understanding the dynamics of digital transformation in rural areas and its implications for achieving the Village Sustainable Development Goals (SDGs).